The Physical Fitness of Regional Student Sports Week Basketball Male Athletes in Kepahiang Regency - Yahya Eko Nopiyanto; Dian Pujianto; Meza Andriyani (Ilmu Olahraga, 2022)
The physical fitness of regional student sports week basketball male athletes in Kepahiang regency is the main goal to be achieved in this study. The research method used is descriptive quantitative with a survey approach. The population in this study were all male basketball athletes, totaling 15 athletes. Total sampling was used in this study to determine the number of samples involved in this study. So 15 athletes were involved in the study as research samples. Data collection techniques using the Indonesian physical fitness test. While the instruments used include a 60-meter running test, pull-ups, sit-ups, vertical jumps, and a 1.2 km run. The components of physical fitness that were taken in this study consisted of components of speed, hand muscle strength, abdominal muscle endurance, leg muscle power, and aerobic endurance. Data analysis used descriptive percentage analysis by looking at the frequency table and categories of physical fitness for male athletes aged 17-19 years. The results of the study describe that the speed aspect is in the medium category (53%), the arm muscle strength aspect is in a good category (80%), and the abdominal muscle strength aspect is in a good category (47%), the leg muscle power aspect is in a good category. (47%), the aspect of endurance is in the moderate category of 60%. So it can be concluded that the physical fitness of regional student sports week basketball male athletes in Kepahiang regency is a medium category.